Customized versus Population Growth Standards for Morbidity and Mortality Risk Stratification Using Ultrasonographic Fetal Growth Assessment at 22 to 29 Weeks' Gestation - Blue, Nathan R.; Grobman, William A.; Larkin, Jacob C.; Scifres, Christina M.; Simhan, Hyagriv N.; Chung, Judith H.; Saade, George R.; Haas, David M.; Wapner, Ronald; Reddy, Uma M.; Mercer, Brian; Parry, Samuel I.; Silver, Robert M. (American Journal of Perinatology, 2020)
Objective The aim of study is to compare the performance of ultrasonographic customized and population fetal growth standards for prediction adverse perinatal outcomes.Study Design This was a secondary analysis of the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-Be, in which l data were collected at visits throughout pregnancy and after delivery. Percentiles were assigned to estimated fetal weights (EFWs) measured at 22 to 29 weeks using the Hadlock population standard and a customized standard (www.gestation.net). Areas under the curve were compared for the prediction of composite and severe composite perinatal morbidity using EFW percentile.Results Among 8,701 eligible study participants, the population standard diagnosed more fetuses with fetal growth restriction (FGR) than the customized standard (5.5 vs. 3.5%, p < 0.001). Neither standard performed better than chance to predict composite perinatal morbidity. Although the customized performed better than the population standard to predict severe perinatal morbidity (areas under the curve: 0.56 vs. 0.54, p = 0.003), both were poor. Fetuses considered FGR by the population standard but normal by the customized standard had morbidity rates similar to fetuses considered normally grown by both standards.The population standard diagnosed FGR among black women and Hispanic women at nearly double the rate it did among white women (p < 0.001 for both comparisons), even though morbidity was not different across racial/ethnic groups. The customized standard diagnosed FGR at similar rates across groups. Using the population standard, 77% of FGR cases were diagnosed among female fetuses even though morbidity among females was lower (p < 0.001). The customized model diagnosed FGR at similar rates in male and female fetuses.Conclusion At 22 to 29 weeks' gestation, EFW percentile alone poorly predicts perinatal morbidity whether using customized or population fetal growth standards. The population standard diagnoses FGR at increased rates in subgroups not at increased risk of morbidity and at lower rates in subgroups at increased risk of morbidity, whereas the customized standard does not.
Keywords: customized fetal growth standard; fetal growth restriction; intrauterine growth curve; perinatal morbidity